Factors affecting consumer intention to use QRIS during the Covid-19 pandemic by using C-TAM-TPB - Ignasius Triutomo Pristya Putra; Ignatius Heruwasto (President University, 2022)
The COVID-19 pandemic has changed consumer behavior. Physical distancing policies have made consumers try to do contactless activities, including purchases to meet their daily needs. The development of economic transactions is now leading to the formation of a cashless society culture, one of which is the use of the QRIS payment system in Indonesia. This study aims to analyze the factors that are influenced by Perceived COVID 19 Risk, which affect the intention to use digital payment QRIS during the pandemic in Indonesia. This study integrates the Theory Acceptance Model (TAM) and Theory Planned Behavior (TPB) C-TAM-RPB Model to find out what factors influence the intention to use QRIS. This research is quantitative research, with a purposive sampling approach used to achieve the research objectives. Data were collected from 236 respondents who knew and had used QRIS through online surveys. The analysis of hypothesis testing used PLS-SEM to evaluate the effect of research hypotheses. The expected result is how the Perceived COVID 19 Risk affects the factors of intention to use QRIS. Thus, it can help to see the factors that influence consumer behavior using QRIS and optimize the use of QRIS in business commercial activities during the COVID 19 pandemic.